Changes of Socio-demographic data of clients seeking genetic counseling for hereditary breast and ovarian cancer due to the "Angelina Jolie Effect". Issue 1 (December 2016) - Staudigl, Christine; Pfeiler, Georg; Hrauda, Katharina; Renz, Romana; Berger, Andreas; Lichtenschopf, Renate; Singer, Christian; Tea, Muy-Kheng
Abstract Background The purpose of this study was to evaluate socio-demographic characteristics of clients claiming genetic counseling for hereditary breast and ovarian cancer (HBOC) in Austria. Furthermore, changes of these parameters before and after Angelina Jolie's (AJ) disclosure of carrying a BRCA mutation were evaluated. Methods In this prospective, nonrandomized study 268 consecutive clients seeking genetic counseling for HBOC at the Medical University of Vienna, Department of Obstetrics and Gynecology, Vienna, Austria between June 2012 and June 2014 were included. Socio-demographic data and source of information about HBOC and genetic counseling were evaluated. First, socio-demographic parameters were compared to the general Austrian population. Second, changes in these parameters after AJ's public disclosure of carrying a BRCA mutation were analyzed. Results Subjects were more frequent female, younger and higher educated in comparison to Austria's general population (p  < 0.001). Furthermore, level of education in participants was higher before than after AJ's disclosure (p  = 0.046). Most clients were informed about genetic counseling by physicians. As expected, after AJ's public announcement patients were more frequent advised to genetic counseling by social media (p  = 0.043) and family or friends (p  = 0.010) than before. Conclusions In this present study we could demonstrate that particularly younger and female participants with high educational level attended significantly more often genetic counseling for HBOC. Increased presence of HBOC in media since AJ's disclosure of carrying a BRCA mutation had lead that information and awareness about HBOC was obtained by a wider audience from different social background.